ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP FINANCIAL STATEMENT FRAUD (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019- 2021) - Murran Afif Wahyudi; Totok Dewayanto (Diponegoro Journal of Accounting, 2023)
This study aims to obtain empirical evidence and to analyze the effect of Good Corporate Governance’s mechanism such as board size of commissioners, board composition of independent commissioners, audit committee meeting, board of commisioners meeting, and managerial ownership on likelihood of financial statement fraud. The sampling method used in this study is purposive sampling method. Data collected from annual report. The data then analized using logistics regression analysi. The results of analysis this study indicate that board size of commissioners, composition of independent commissioners and managerial ownership have a significant negative effect on likelihood of financial statement fraud. While board of commisioners meeting have a significant positive effect and managerial ownership have no significant effect on likelihood of financial statement fraud.